Solar powered wakaf lamp / Ahmad Bazli Bakri, Fatin Syahirah Abdul Rahim and Ahmad Zulfadhli Ahmad Zamri - Bakri, Ahmad Bazli; Abdul Rahim, Fatin Syahirah; Ahmad Zamri, Ahmad Zulfadhli (2015)
Solar Powered Wakaf Lamp is a project that is applied at the gazebo to help reduce electricity bill. This project uses renewable energy method. Electrical energy harvested from solar panel is stored in a battery and uses to power up an LED bulb at night. The LED bulb is triggered by an infrared sensor in the dustbin. Plastic bottles or any waste material interferes the sensor thus triggering the LED bulb circuit to light up. Basically , plastic bottles are required to on the LED light. This project helps to save energy along with implementing recycle activity to all the students in Universiti Teknologi MARA (UiTM).